Effect of Sociodemographic Factors on Self-Monitoring of Blood Glucose Behavior of People with Type 2 Diabetes Mellitus - Rondhianto Rondhianto; Ana Nistiandani; Latifah Nur Jannah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2023)
Self-monitoring of blood glucose (SMBG) is important in diabetes self-management to achieve better HbA1c control and decrease complications, morbidity, and mortality in people with type 2 diabetes mellitus (T2DM). SMBG behavior can be influenced by various factors, one of which is sociodemographic factors. This study aimed to analyze the sociodemographic factors that influence the behavior of self-monitoring blood glucose in patients with T2DM. The cross-sectional study was conducted in ten health centers in Jember Regency with a sample size of 130 respondents using multistage random sampling. The independent variable is sociodemographic factors (age, gender, marital status, education level, income level, family type, and ethnicity), while the dependent variable is SMBG behavior. The instrument used was the Self-Monitoring Blood Glucose Questionnaire (SMBG-Q). Data were analyzed by multiple logistic regression. Most respondents had SMBG behavior in the good category (64.6%). Sociodemographic factors simultaneously had an influence on SMBG behavior (p = 0.001 < α = 0.05; R2 = 0.324). The sociodemographic factor that significantly affects SMBG behavior partially is ethnicity (p = 0.001 < α = 0.05). Meanwhile, age, gender, marital status, education level, income level, and family type did not have a significant partial effect (p = 0.095; p = 0.149; p = 0.083; p = 0.359; p = 0.507; p = 0.152 > α = 0.05). The sociodemographic factor that influences SMBG behavior is ethnicity. Therefore, efforts to improve SMBG behavior must pay attention to values and culture to improve the self-monitoring blood glucose behavior of people with T2DM. Keywords: Type 2 diabetes mellitus; self-monitoring blood glucose behavior; sociodemographic